The Influence of Executive Compensation, Board of Directors Compensation and Share Ownership on Tax Aggressivity - Arji Saputra; Indawati (MultiTech Publisher, 2023)
This study aims to examine the effect of executive compensation, directors compensation and share ownership on tax aggressiveness. This study uses the dependent variable tax aggressiveness and independent variable executive compensation, directors compensation and share ownership. Tax aggressiveness is an effort made by companies to reduce tax payments. The population in this study are energy sector companies listed on the Indonesian stock exchange for the period 2017 – 2021. The total population or banking sector companies are 66 companies. From the total population, a purposive sampling technique was used with several criteria to determine the sample, so that a sample of 23 companies was obtained. The data analysis technique used in this study uses eviews 10 which includes descriptive statistical tests, panel data model analysis, classical assumption tests and hypothesis testing. Based on the test results above, it proves that executive compensation, directors compensation and share ownership have a simultaneous effect on tax aggressiveness. However, partially only directors' compensation has an effect on tax aggressiveness, while executive compensation and share ownership have no effect on tax aggressiveness.